Histone clipping: the punctuation in the histone code. (7th July 2021) - Dhaenens, Maarten
Abstract : Histone clipping was first discovered in the 1960s and still is a lingering mystery. Considering the essential roles of histones in regulating eukaryotic transcription through the histone code, clipping is a post‐translational modification that appeals to the imagination. In this issue of EMBO Reports, Marruecos and colleagues investigate histone H4 clipping during intestinal development (Marruecos et al, 2021), and are providing crucial clues to finally elucidate the intricacies of this elusive modification. Abstract : Functional roles for histone clipping have been rarely described. A study in this issue now identifies histone H4 clipping as essential to regulate chromatin association of IκBα during intestinal development.